Pengaruh Sikap dalam Membentuk Niat Perilaku Hand hygiene pada Perawat di Rumah Sakit - Rondhianto, Rondhianto; Fitriani, Fitriani; Ismara, Ketut Ima (ARTERI : Jurnal Ilmu Kesehatan, 2024)
known to increase hand hygiene compliance. The existence of an intention within a person can give rise to an attitude to behave. The study aims to analyze the influence of hand hygiene behavior attitudes on intentions and the influence of hand hygiene behavior attitudes on hand hygiene compliance and to analyze the mediating effect of intentions on attitudes towards hand hygiene behavior. The method in this research uses a cross-sectional study. The research location is at one of the Jember Regency government hospitals in June – July 2023. The population in this study were all nurses who provided direct services to patients using a sampling technique using a total sampling of 116 respondents. This research data analysis is path analysis with SEM-PLS using smart-pls software. The results of this research showed that the majority of respondents were aged 26-35 years (52.59%), male (56.03%), diploma education level (43.97%), working period 1-5 years (39.66 %), and have received hand hygiene training (82.76%). The model prepared was fit (SRMR = 0.062 and NFI = 0.911). Hand hygiene behavior attitude significantly affects intentions (p = 0.031). Hand hygiene behavior attitude has a significant effect on hand hygiene behavior (p = 0.000). Intention was able to mediate hand hygiene behavior attitudes towards hand hygiene behavior (p = 0.033). The study concludes that attitudes can directly influence or be mediated by the intention to hand hygiene behavior. Future researchers could research on variables other influence intentions to behave can improve hand hygiene behavior. The intervention for nurses can involve training on hand hygiene and providing posters or other reminders to encourage hand hygiene behavior.